O patrimônio histórico e cultural sob a ótica do poder público no Vale do Taquari/RS - Lopes, Sérgio Nunes (2012)
This work analyzes the public power position in the face of the Historical and Cultural Vale do Taquari/RS. The study focuses on three towns: Bom Retiro do Sul, in the South; Arroio do Meio, in the center, and Arvorezinha, in the North. The laws and published decrees were analyzed, since political emancipation of each one of the towns until nowadays. The reflection establishes a dialogue between the scientific concepts used in the analysis of the object and the definitions present in official documentations. It is also part of the study, the practical implications from official measures concerning the Historical and Cultural Heritage. Such unfolding is visible in the press and in supplementary laws that legitimizes the first impressions of the administrators regarding the Heritage.